Iridium-Catalyzed Asymmetric Allylation of Indoles via Kinetic Resolution of 1-Alken-4-yn-3-ols - Sawano, Takahiro; Yasumura, Yuki; Kuwabara, Kyohei; Sugiura, Hikaru; Takahashi, Kana; Ishikawa, Eri; Takeuchi, Ryo (Synlett, 2023)
We report the iridium-catalyzed asymmetric allylation of indoles via kinetic resolution of 1-alken-4-yn-3-ols to form chiral 1-alken-4-yn-3-ols and branched allylated products with high selectivity. 1-Alken-4,6-diyn-3-ol was also found to be suitable for this asymmetric allylation and gave the products in high yield and enantioselectivity. Other nucleophiles such as a malonic ester and a thiol, besides indoles, reacted to give allylated products and 1-alken-4-yn-3-ols with high enantioselectivities.
Keywords: iridium; asymmetric catalysis; allylation; 1-alken-4-yn-3-ols; indoles